Potret teacherpreneurship guru bahasa jerman di Indonesia - Qur'aniwati, Diah; Sobara, Iwa (Fakultas Sastra, 2023)
Abstract: In the 21st century, teachers face many problems that require change from the teachers themselves. The challenges faced by teachers can turn into opportunities when teachers become teacherpreneurs. The purpose of this research is to gather information about teacherpreneurship of German teachers in Indonesia. There were 70 German teachers in various cities in Indonesia who participated in this research. Open questionnaires were distributed to the respondents. The questionnaire was then used to collect data and then evaluated descriptively and qualitatively. German teachers in various cities in Indonesia actually have the potential to become teacherpreneurs. The potentials that have been developed by the respondents include: private German language courses (online and offline), translators, employees at travel agencies, content creators on social media, etc. However, many respondents said they did not have much time for teacherpreneurship because they had to spend their time at school. Keywords: teacherpreneurship, German teacher, opportunities, challenges